Study based on bibliometric analysis: potential research trends in fluid management for sepsis - Liu, Sihan; Pei, Haoting; Wang, Jing; Qiao, Lujun; Wang, Hao (Frontiers in Medicine, 2025)
The objective of this study is to investigate the potential and evolving trends in fluid management for patients with sepsis, utilizing a bibliometric approach. Scholarly articles pertaining to fluid therapy for sepsis patients were extracted from the Web of Science (WoS) database as of June 1, 2024. The R software package, "Bibliometrix," was utilized to scrutinize the primary bibliometric attributes and to construct a three-field plot to illustrate the relationships among institutions, nations, and keywords. The VOSviewer tool was employed for author analysis, keyword co-occurrence analysis, and data visualization. Additionally, CiteSpace was used to calculate citation bursts and keywords.A comprehensive retrieval from the Web of Science (WoS) database yielded a total of 2,569 publications. The majority of these articles were predominantly published by two countries, namely the United States (US) and China. Among the myriad of journals, Critical Care and Journal for Intensive Care Medicine emerged as the most prolific. In terms of institutional contribution, the University of California System stood out as the most productive. Recent analysis of keywords revealed a significant citation burst for terms such as "balanced crystalloids" and "critically ill children".